2020
DOI: 10.1097/md.0000000000021019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lncRNA FEZF1-AS1 as a potential biomarker for diagnosis of non-small-cell lung carcinoma

Abstract: Diagnosis of numerous cancers has been closely linked to the expression of certain long non-coding RNAs. This study aimed to evaluate levels of plasma FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1) relative to non-small-cell lung carcinoma (NSCLC) diagnosis. The level of FEZF1-AS1 in the blood plasma of 126 NSCLC patients and 62 healthy controls was examined by quantitative real-time polymerase chain reaction. Plasma FEZF1-AS1 of the NSCLC group was increased compared with that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, the occurrence of early metastasis in lung cancer patients is of great importance for the selection of appropriate treatment plans. Currently, noninvasive tests such as long-non-coding RNA (Lnc RNA), neuron-specific enolase (NSE), circulating tumor DNA (ct DNA) and microRNAs have good diagnostic value for early diagnosis and cancer staging of lung cancer (11)(12)(13)(14), however, there are few reports on the diagnosis of metastasis in non-small cell lung cancer. Liquid biopsy and tissue biopsy are the gold standard for cancer diagnosis, however, due to the limitations of their operation such as invasiveness, complexity, inability to monitor longitudinally and continuous monitoring, and clinical variability of patients (15,16), monitoring cannot be routinely performed in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the occurrence of early metastasis in lung cancer patients is of great importance for the selection of appropriate treatment plans. Currently, noninvasive tests such as long-non-coding RNA (Lnc RNA), neuron-specific enolase (NSE), circulating tumor DNA (ct DNA) and microRNAs have good diagnostic value for early diagnosis and cancer staging of lung cancer (11)(12)(13)(14), however, there are few reports on the diagnosis of metastasis in non-small cell lung cancer. Liquid biopsy and tissue biopsy are the gold standard for cancer diagnosis, however, due to the limitations of their operation such as invasiveness, complexity, inability to monitor longitudinally and continuous monitoring, and clinical variability of patients (15,16), monitoring cannot be routinely performed in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have revealed that lncRNAs play critical roles in the carcinogenesis and cancer progression of a variety of cancers, including GC ( Yu and Rong, 2018 ; Ghafouri-Fard and Taheri, 2020 ). For example, FEZF1-AS1, a top overexpressed lncRNA in colorectal cancer, has been found to be involved in the initiation and progression of various cancers including colorectal carcinoma ( Chen et al, 2016 ; Bian et al, 2018 ), non-small cell lung cancer ( Huang et al, 2020 ) and gastric cancer ( Wu et al, 2017 ). However, the molecular mechanism of FEZF1-AS1 plays in GC, particularly in chemoresistance of GC cells has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…As described in previously studies ( Bian et al, 2018 ), lncRNA FEZF1-AS1 was upregulated in primary colorectal carcinoma (CRC), non-small cell lung cancer (NSCLC) as well as GC tissues and cells, and the overexpression of ncRNA FEZF1-AS1 was correlated with poor prognosis. Dysregulation of lncRNA FEZF1-AS1 promoted the proliferation and migration of CRC ( Bian et al, 2018 ), NSCLC ( Huang et al, 2020 ), and GC cells ( Hui et al, 2020 ). Furthermore, knock down of lncRNA FEZF1-AS1 significantly suppressed the proliferation and invasion of tumor cells ( Chen et al, 2016 ; Bian et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with those studies of circulating lncRNAs in diagnosing NSCLC (29)(30)(31)(32), our study is unique for the following reasons: Firstly, we selected 31 lung cancer related lncRNAs based on the previous studies and screened the expression of these lncRNAs in the plasma, which make it easier to obtain effective diagnostic markers for lung cancer. Secondly, we included not only healthy controls but also benign lung diseases in the control group.…”
Section: Discussionmentioning
confidence: 99%